KAJIAN MATERIAL SEDIMEN PANTAI BALIKPAPAN UNTUK MENGETAHUI VARIASI UKURAN BUTIR PARTIKEL PASIR (SAND) SEDIMEN - Rohima Sera Afifah; Karmila Karmila; Nuruddin Kafy El-Ridlo (Universitas Lambung Mangkurat, 2021)
Along the Balikpapan Beach, there are abundant sand-sized sediment particles. Sand is one of the unconsolidated sediment grains based on fractions on the Wentworth Scale. Unconsolidated Sediment is defined as Loose Material and/or sedimentary rocks that is not yet solid. Balikpapan Beach, based on the Regional Geological Map of Balikpapan sheet, formed the Alluvium Formation (abbreviated as Qa) of the Holocene Epoch, Quaternary. Alluvium formation (Qa) has an arrangement of rocks in the form of pebbles, gravel, sand, and clay. Samples of Unconsolidated Sediment or loose material and sedimentary rocks that is not yet solid are determined for grain size variations using the Sieving method. The Seiving method or Sieve Test is a method for determining the size of the grains which will then be viewed on a scale and followed by the amount of grain size data that will be presented in graphical form to facilitate the type of grain size that dominates. The research focused on how the grain size on Balikpapan Beach based on the Wentworth Scale and Sorting data after the Sieve Test. Sieve Test results measured Mesh#10, Mesh#20, Mesh#40, Mesh#60, Mesh#120, Mesh#200 and Filter Analysis of the relationship between Filter Diameter and Retained Percentage as follows: Granule by 3.53%, Sand (Very Coarse Sand by 3.53%, Coarse Sand by 4.75%, Medium Sand by 13.26%, Fine Sand by 66.26%, Very Fine Sand by 5.15%) and Coarse Silt by 3.35%. Therefore, particles in the area of research with the Sieve Test were dominated by Fine Sand particles. Fine Sand with grain size 0.125 – 0.25 mm tested with a filter diameter of 0.125 mm got a Retained Weight of 331.29 gr, Retained Weight Precentage of 66.26%.